Analysis Of Market Orientation ON Tourism - Indra Perdana Wibisono; Edy Wahyudi Wahyudi; Siti Khotimah Khotimah (Indonesian Journal Of Business And Economics, 2021)
This research aims to determine the analysis of market orientation in the tourism industry. The object of this research is Wisata Bahari Lamongan and the informants in this study were three people who were chosen by the researchers. This type of research uses a descriptive type of research with a qualitative approach. The analytical tool used is taxonomic analysis domain analysis. Taxonomic analysis is a tool used to analyze the overall data from the research object based on a predetermined domain and then a more in-depth analysis. The results of this analysis explain that Wisata Bahari Lamongan considers competitors as a benchmark or reflection, this can be seen from cooperative activities. Wisata Bahari Lamongan has a different potential from other places. Wisata Bahari Lamongan has several departments in the organizational structure, one of which is the Marketing department. In practice, the Marketing department has many online and offline based activities. In terms of products and facilities, Wisata Bahari Lamongan always issues new innovations every year and makes periodic improvements. They cooperates with several competitors by marketing promotional media at each tourist spot. They carry out activities that adopt technology, both marketing activities and internal activities, so that tourist destinations become more open and able to compete equally with others.